A new nickel-ceria composite for direct-methane solid oxide fuel cells - Zhu, H.; Wang, Wei; Ran, R.; Shao, Zongping (Elsevier Ltd, 2013)
Various Ni-LaxCe1-xOy composites were synthesized and their catalytic activity, catalytic stability and carbon deposition properties for steam reforming of methane were investigated. Among the catalysts, Ni-La0.1Ce0.9Oy showed the highest catalytic performance and also the best coking resistance. The Ni-LaxCe1-xOy catalysts with a higher Ni content were further sintered at 1400 degrees Celcius and investigated as anodes of solid oxide fuel cells for operating on methane fuel. The Ni-La0.1Ce0.9Oy anode presented the best catalytic activity and coking resistance in the various NieLaxCe1-xOy catalysts with different ceria contents. In addition, the Ni-La0.1Ce0.9Oy also showed improved coking resistance over a Ni-SDC cermet anode due to its improved surface acidity. A fuel cell with a Ni-La0.1Ce0.9Oy anode and a catalyst yielded a peak power density of 850 mW cm-2 at 650 degrees Celcius while operating on a CH4-H2O gas mixture, which was only slightly lower than that obtained while operating on hydrogen fuel. No obvious carbon deposition or nickel aggregation was observed on the Ni-La0.1Ce0.9Oy anode after the operation on methane. Such remarkable performances suggest that nickel and La-doped CeO2 composites are attractive anodes for direct hydrocarbon SOFCs and might also be used as catalysts for the steam reforming of hydrocarbons.